Pengaruh Gaya Hidup Dan Ketersediaan Produk Terhadap Keputusan Pembelian Sepatu Merek Vans Di Kota Langsa - Akbar, Muhammad Agil; Junaida, Erni; Lindung Bulan, Tengku Putri (Universitas Labuhanbatu, 2022)
This study intends to determine the effect of lifestyle and product availability on the decision to purchase Vans brand shoes in Langsa City. The number of samples in this study were 96 respondents. In this study using an analytical method consisting of multiple linear regression analysis, t test, F test and the coefficient of determination (adjusted r2). From the research results, it was found that the regression equation Y = 2.193 + 0.829 X1 + 0.377 X2, this means that a constant value of 2.193 indicates the value of the purchase decision before being influenced by lifestyle variables and product availability. The results of the t test stated that the lifestyle variable (X1) had a significant effect on the decision to purchase Vans brand shoes in Langsa City with a tsig value of 0.000 > 0.05, the product availability variable (X2) had a significant effect on the decision to purchase Vans brand shoes in Langsa City with tsig value of 0.011>0.05. The results of the F test stated that lifestyle and product availability simultaneously had a significant effect on purchasing decisions for Vans brand shoes in Langsa City, the Fsig value was 0.000 <0.05. The results of the coefficient of determination test (adjusted r2) show that lifestyle and product availability variables influence the decision to purchase Vans brand shoes in Langsa City by 63.9% and the remaining 36.1% is influenced by other variables such as product quality, brand image and others.